PREVALENSI OBESITAS PADA REMAJA SMA YPKM DI KOTA MANADO - Chandra, Donald Andreas; Manampiring, Aaltje E.; ., Fatimawali (Universitas Sam Ratulangi, 2014)
Abstract: Obesity is defined as a condition in which an abnormal accumulation of fat in adipose tissue or redundant to some extent which can be harmful to health. One of the risk factors of obesity are environmental factors, a category including behavioral or lifestyle patterns (e.g. what to eat and how many times a person eats and how their activities) are experienced by many young people in the city of Manado. The purpose of this study was to determine the prevalence of obesity in adolescents. This study used cross sectional method with descriptive approach, the sampling technique which used is simple random sampling. The research sample is 100 students who met the inclusion criteria were age 13-18 years, willing to be sampled. Data retrieval is done by measuring waist circumference, weight, and height. Based on the measurement of waist circumference in 100 populations found 10 people students were obesity with a percentage of 10% which consist of 6 boys with the percentage of 6% and 4 girls with a percentage of 4%. Meanwhile, if measured by BMI CDC 2000 found 9 students who are obesity by 9% which consists of 6 boys with a percentage of 6% and 3 girls with a percentage of 3%. Keyword: Obesity, adolescents.Â Â Abstrak: Obesitas didefinisikan sebagai suatu kondisi akumulasi lemak yang tidak normal atau berlebihan di jaringan adiposa sampai kadar tertentu sehingga dapat merusak kesehatan. Salah satu faktor resiko obesitas adalah faktor lingkungan, dimana termasuk perilaku/pola gaya hidup (misalnya apa yang dimakan dan berapa kali sesesorang makan serta bagaimana aktifitasnya) yang banyak dialami oleh para remaja di Manado. Tujuan penelitian ini adalah untuk mengetahui prevalensi obesitas pada remaja. Penelitian ini menggunakan metode cross sectional dengan pendekatan dekskriptif. Teknik pengambilan sampel yang digunakan adalah dengan menggunakan cara simple random sampling. sampel penelitian sebanyak 100siswa-siswi yang memenuhi kriteria inklusi yang berusia 13-18 tahun, bersedia menjadi sampel. Pengambilan data dilakukan dengan cara pengukuran lingkar pinggang, berat badan, dan tinggi badan. Berdasarakan hasil pengukuran lingkar pinggang pada 100 populasi didapatkan 10 orang siswa-siswi mengalami obesitas dengan presentase sebesar 10% yang terdiri dari 6 orang siswa dengan presentase 6% dan 4 orang siswi dengan presentase sebesar 4%. Sedangkan jika diukur berdasarkan IMT CDC 2000 didapati 9 siswa-siswi yang mengalami obesitas dengan presentase sebesar 9% yang terdiri dari 6 orang siswa dengan presentase 6% dan 3 orang siswi dengan presentase sebesar 3%. Kata kunci: Obesitas, Remaja